Ankfy1 Is Involved in the Maintenance of Cerebellar Purkinje Cells - Chang, Liansheng; Soomro, Shahid Hussain; Zhang, Hongfeng; Fu, Hui (Frontiers in Cellular Neuroscience, 2021)
Purkinje cells are critical for the function of cerebellum. The degeneration of Purkinje cells leads to defects in motion control. We have found that Purkinje cells specifically express Ankfy1 protein during development and in adult. This protein seems to play minor functions during development as Ankfy1 knockout mice appear normal till adult. However, at 9-month-old, knockout mice showed abnormal cerebellum with reduced vermis size and developed defective motor function. Further investigation demonstrated that the cerebellum of the mutant mouse has lost most of its Purkinje cells, while other cerebellar cells remained largely normal. Our data suggested that the Ankfy1 might be important for the maintenance of cerebellar Purkinje cells.